Vulnerable Marine Ecosystems, Communities, and Indicator Species: Confusing Concepts for Conservation of Seamounts - Watling, Les; Auster, Peter J. (Frontiers in Marine Science, 2021)
The concept of “vulnerable marine ecosystem” (VME) was included in United Nations (UN) General Assembly Resolution 61/105 as part of an international effort to minimize the effects of benthic fisheries on the high seas. However, defining a VME was left to be developed by technical guidance to the UN Food and Agricultural Organization. In that venue certain categories of organisms were deemed to be indicator species, suggesting that areas with those species would be considered VMEs with subsequent management measures implemented to conserve those ecosystem attributes. We note that on seamounts VME indicator species can be distributed widely, in dense clusters or sparse. A dense cluster, for example, of scleractinian corals or sponges, is most often referred to as a VME, but we argue that any such dense cluster is not an ecosystem, rather it is a community, likely one of many that make up the ecosystem. Other communities on the seamount that are not part of that dense cluster could include many small species (some yet to be discovered) who are also part of the ecosystem because they are part of the web of interactions and flow of materials/energy on the seamount. We also suggest that a seamount ecosystem might extend over several or many seamounts in a biogeographic area. We conclude that the term “ecosystem” in the VME concept outlined by the United Nations needs to be re-evaluated from a classical ecological perspective.